Carbohydrates Used in Polymeric Systems for Drug Delivery: From Structures to Applications - Xiangjie Di; Xiao Liang; Chao Shen; Yuwen Pei; Bin Wu; Zhiyao He (MDPI AG, 2022)
Carbohydrates, one of the most important compounds in living organisms, perform numerous roles, including those associated with the extracellular matrix, energy-related compounds, and information. Of these, polymeric carbohydrates are a class of substance with a long history in drug delivery that have attracted more attention in recent years. Because polymeric carbohydrates have the advantages of nontoxicity, biocompatibility, and biodegradability, they can be used in drug targeting, sustained drug release, immune antigens and adjuvants. In this review, various carbohydrate-based or carbohydrate-modified drug delivery systems and their applications in disease therapy have been surveyed. Specifically, this review focuses on the fundamental understanding of carbohydrate-based drug delivery systems, strategies for application, and the evaluation of biological activity. Future perspectives, including opportunities and challenges in this field, are also discussed.